Analisis Penggunaan Indeks Visa terhadap Minat Bekerja bagi Warga Negara Asing (WNA) di Indonesia: Studi terhadap Kesalahan Penggunaan Indeks Visa untuk Tujuan Pekerjaan - Widya Hafizhah; Butar Butar, Putri Lauren; Muhammad Rizky Fauzi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
The mobility of foreign nationals (WNA) entering Indonesia is increasing along with the development of globalization, investment, and international cooperation. In the Indonesian immigration system, every foreign national entering Indonesia is required to use a visa appropriate to their purpose of entry. One important instrument in this regulation is the visa index, which indicates the types of activities that visa holders can engage in while in Indonesia. However, in practice, various cases of incorrect use of the visa index are still found, particularly when foreign nationals use visit visas or business visas for work activities. This condition can lead to violations of immigration provisions and has the potential to affect the orderly management of foreign workers in Indonesia. This study aims to analyze the legal regulations regarding visas and the visa index in the Indonesian immigration system, examine the phenomenon of incorrect use of the visa index by foreign nationals for work purposes, and identify the causal factors and government efforts to prevent visa misuse. This study uses a normative legal research method with a qualitative approach. The approaches used include a statutory regulatory approach, a conceptual approach, and a case approach. The data used is secondary data obtained through a literature review of laws and regulations, scientific journals, books, and official sources related to immigration policy in Indonesia. The results of the study indicate that errors in the use of the visa index by foreign nationals are caused by several factors, including a lack of understanding of immigration regulations, the complexity of work visa application procedures, the need for foreign workers in certain sectors, and limited supervision. Therefore, increased supervision, strict law enforcement, and the dissemination of immigration regulations are needed to ensure that visa use by foreign nationals is in accordance with applicable laws.